Znanje kot pravno zavarovana vrednota - tempora mutantur - Ilešič, Marko (Podjetje in delo, 2013)
The traditional understanding requires the necessity of effective legal protection of knowledge, in particular by the protection of intellectual property. However, the question which arises more and more frequently is whether really every use of somebody elses knowledge is unlawful, bearing in mind that every creation of knowledge is based on the creativity of humankind in the past. There is an idea emerging that the protection of knowledge by means of granting a monopoly to its author does not correspond to the modern era, taking into account its information and digital dimensions. The author raises the question whether this monopoly (still, with the same scope, using the same legal instruments) is still justified. After the survey of certain development in the European law the author comes to the conclusion that there have been changes in our minds as well; therefore, the starting point presuming that any use of somebody elses knowledge is unlawful as a rule, and seeking the balance of interests is only the next step, is probably obsolete.
Keywords: avtorsko pravo; intelektualna lastnina; knowledge; pravna ureditev; znanje; znanstvenoraziskovalno delo